The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1590/s1519-38292014000400013
|View full text |Cite
|
Sign up to set email alerts
|

Construtos teóricos de Paulo Freire norteando as estratégias de promoção à amamentação

Abstract: Objetivos: refletir sobre a inserção dos construtos teóricos de Paulo Freire, o diálogo, a ética e a problematização, na promoção da amamentação, envolvendo a rede social da mulher. Métodos: ensaio teórico que consiste em exposição lógica, argumentativa e crítica, conduzida pelo pensamento freireano integrado ao fenômeno da amamentação para subsidiar novos caminhos que poderão permear as ações promotoras desta prática. Resultados: o desenvolvimento de ações educativas alicerçadas em um referencial teórico pode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
6

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 16 publications
(14 reference statements)
0
6
0
6
Order By: Relevance
“…It is important that the information be worked in a diluted form and according to the moment the woman is experiencing, using participatory methodologies that strengthen the participation, reflection, criticality and empowerment of the subjects (22) . The mothers of this study reported that they received support from the health professionals for breastfeeding, which is an instrumental support, since it includes practical help, transmission of knowledge and encouragement for the practice of breastfeeding.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is important that the information be worked in a diluted form and according to the moment the woman is experiencing, using participatory methodologies that strengthen the participation, reflection, criticality and empowerment of the subjects (22) . The mothers of this study reported that they received support from the health professionals for breastfeeding, which is an instrumental support, since it includes practical help, transmission of knowledge and encouragement for the practice of breastfeeding.…”
Section: Discussionmentioning
confidence: 99%
“…In view of this, it is evident that educational action is a strategy to promote breastfeeding; nevertheless, these programs are often carried out in a unidirectional form, without valorizing the woman as protagonist in this process, or her prior knowledge. Therefore, it is necessary to find ways to involve all subjects participating in strategies to promote breastfeeding to take into account their culture, habits and beliefs (22) . This study also showed that the puerperal mothers were guided by the professionals in the joint lodging and their family as to the correct handling of the breast and position of the baby during breastfeeding.…”
Section: Discussionmentioning
confidence: 99%
“…In another study, Linhares et al 19 show that many women have sought knowledge and practices experienced by other people, as integral parts of this process, and professionals have been losing their credibility. Popular knowledge, habits, cultures, customs and beliefs, more and more, have positively or not favored their own continuity, which generates the need for the elaboration of strategies to promote breastfeeding, in their individuality and in the community.…”
Section: The Mothers Profile and The Mapping Of Their Networkmentioning
confidence: 99%
“…The study requires to "take a serious and curious attitude towards a problem" ( [16], p. 58). Thus, the Problematization phase, proposed by [8], in order to be applied to health education activities, emerges from generating issues proposed by animators/researchers, leading to an immersion in the subject from the experiences of the group, full of personal and collective meanings intrinsic to the involvement of each member in the learning process.…”
Section: Discussionmentioning
confidence: 99%
“…The application of a Culture Circle can provide an intense flow of critical, reflective and mobilizing knowledge committed to a renewed practice in Health education [16]. According to Paulo Freire, idealizer of the Culture Circles, the use of this pedagogical proposal is essential to the construction of health education strategies, enabling to assume that teenagers have knowledge, values, principles and feelings and, at the same time, understanding of their responsibility to transform reality [8].…”
Section: Discussionmentioning
confidence: 99%